Achieving Persistent, Efficient, and Robust Room-Temperature Phosphorescence from Pure Organics for Versatile Applications - He, Zihan (Advanced materials (Deerfield Beach, Fla.), 2019)
© 2019 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.